2005
DOI: 10.1002/pssb.200562214
|View full text |Cite
|
Sign up to set email alerts
|

Optical response of Ag‐induced reconstructions on vicinal Si(111)

Abstract: The optical response of the Si(111)-(3 × 1) -Ag surface has been studied for the first time with reflectance anisotropy spectroscopy (RAS). A single domain surface was obtained by depositing <1 ML of Ag onto a vicinal Si(111) substrate at 870 K. A significant optical anisotropy develops around 2.2 eV which is related to the formation of the 3 × 1 structure. This surface was then used as a template to grow onedimensional (1D) arrays of Ag nanodots, and also 3D Ag islands, by depositing 0.5 ML, and higher, cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…The computed RA spectrum for the (3 × 1)Ag surface is in good agreement with previously reported experimental RA data for this surface; 16,17 the RA spectrum for the (3 × 1)Li surface has not been reported in the literature, however, strong similarities in the surface electronic structures of the Ag and Li systems and their surface dielectric functions result in similar predicted RA spectra. The origins of the features of the RA spectra below the bulk band gap are identified in terms of transitions between surface states associated with the HCC and chains of Li or Ag atoms.…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations
“…The computed RA spectrum for the (3 × 1)Ag surface is in good agreement with previously reported experimental RA data for this surface; 16,17 the RA spectrum for the (3 × 1)Li surface has not been reported in the literature, however, strong similarities in the surface electronic structures of the Ag and Li systems and their surface dielectric functions result in similar predicted RA spectra. The origins of the features of the RA spectra below the bulk band gap are identified in terms of transitions between surface states associated with the HCC and chains of Li or Ag atoms.…”
Section: Introductionsupporting
confidence: 89%
“…16 We have also shown that one particular surface state, state S 4 in Figs. 3 and 4, is the key vacant state for sub-band-gap optical transitions in this system.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Vicinal, wedged n-type Si(111) samples offcut by 1 towards the ½ " 1 " 1 2 direction were cleaned by heat treatment under ultrahigh vacuum (UHV), and a predominantly single domain Sið111Þ-ð4 Â 1Þ-In structure was grown by depositing In on the clean Si surface at 670 K. The surface order and the phase transition were monitored in situ with RAS, which has been shown to be very useful in monitoring the surface reconstructions of Si(111) [27]. The RAS measurements indicated that the dominant domain occupied about 80% of the surface.…”
mentioning
confidence: 99%